Early-life mortality rates in Brazil and progress toward meeting related sustainable development goals: a nationwide population studyResearch in context - Aline de Siqueira Alves Lopes; Emmanuelle Lira Cariry; Débora Fontes Leite; Lucas Barbosa de Santana; José Rodrigo Santos Silva; Victor Santana Santos; Ricardo Queiroz Gurgel (The Lancet Regional Health. Americas)
Summary: Background: Early-life mortality rates have significantly declined since 2000, and sustaining this progress could save over 11 million children's lives worldwide. Achieving uniform reductions in early-life mortality remains a critical public health challenge in Brazil. This study analyzed disaggregated trends in early-life mortality across Brazilian regions and assessed each region's progress toward meeting the Sustainable Development Goals (SDGs) and national targets for Brazil. Methods: This is a population-based analytical and ecological study. We analyzed data from official government information systems for Brazilian regions and states over five consecutive five-year periods between 1998 and 2022. The SDG targets considered were: an under-five mortality rate (U5MR) of 25 per 1000 live births, a neonatal mortality rate (NMR) of 12.0 per 1000 live births, and an infant mortality rate (IMR) of 15.7 per 1000 live births. Brazil's adjusted national targets were: U5MR of 8.3, NMR of 5.3, and IMR of 7.7 per 1000 live births, respectively. We calculated the absolute annual change (AAC) in mortality rates for each five-year interval to assess trends and infer the likelihood of meeting the 2030 targets. Findings: Between 1998 and 2022, U5MR in Brazil declined by 54%, from 32.5 to 15.1 deaths per 1000 live births. The national average met the SDG targets for all age strata, but no state achieved the stricter IPEA targets. From 2018 to 2022, under-five and infant mortality rates showed annual increases (AAC = +0.22 and + 0.10, respectively), while neonatal mortality remained stable (AAC = −0.02). Regional disparities persisted. In 2022, Santa Catarina (South region) had the lowest U5MR (11.5 deaths per 1000 live births), while Roraima (North region) had the highest (24.6 deaths per 1000 live births). Although most states are projected to meet the SDG targets for U5MR by 2030, none are on track to meet the IPEA goals. Interpretation: Despite national progress in meeting SDG targets for early-life mortality, recent increases in under-five and infant deaths and enduring regional inequalities threaten future gains. Sustained improvements will require focused, region-specific strategies to address the social and health determinants driving these disparities. Funding: This research received no specific grant from any funding agency.